O ensino de história na Comunidade Quilombola de Saracura com a implementação da lei 10.639/2003. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study investigates the implementation of Law 10.639/2003 at Nossa Senhora do Livramento School, located in the quilombola community of Saracura, in the municipality of Santarém-PA. The research aims to understand the progress and challenges in applying this legislation, which mandates the teaching of Afro-Brazilian history and culture in schools. The methodology included interviews with the institution’s teachers, an analysis of the school’s Political-Pedagogical Project (PPP), and observation of the pedagogical practices employed. The results indicate that, despite local efforts to implement the law, significant challenges remain, such as the scarcity of adequate teaching materials and the need for continuous teacher training. However, there is a notable appreciation for pedagogical practices that reinforce students' Afro-Brazilian identity, such as the use of thematic murals, the creation of Abayomi dolls, cultural performances, and other activities aimed at strengthening the community’s collective memory. It is concluded that the effective implementation of Law 10.639/2003 in quilombola education requires more structured policies for teacher training, the production of specific teaching materials, and greater involvement of the school community. In this way, progress is made toward building a more inclusive and anti-racist education.
Keywords: Educação Quilombola; Lei 10.639/2003; Ensino de História Afro-brasileira; CNPQ:: CIÊNCIAS HUMANAS